2020
DOI: 10.3892/mmr.2020.11186
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of MYD88 L265P mutation in diffuse large B cell lymphoma via droplet digital PCR

Abstract: To assess the prevalence and prognostic value of myeloid differentiation factor 88 (MYd88) expression and mutational status in diffuse large B cell lymphoma (dlBcl), a total cohort of 100 patients with dlBcl were studied using immunohistochemistry (iHc) and droplet digital polymerase chain reaction (ddPcr), and the association between MYd88 expression and clinicopathological parameters was analyzed. overall, the positive expression rate of MYd88 protein was 38% and the gene mutation rate was 29%. The positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Further studies confirmed such remarkable site-specific occurrence of MYD88 mutation [55,56]. Gastrointestinal DLBCL <5% [60] 11% [40] Absent [40] Primary Bone DLBCL Absent [60] Absent [60] Absent [60] Thyroid gland DLBCL Absent [60] Absent [60] Absent [60] Head and Neck DLBCL Unknown [60] 3.17% (small sample size) [61] Unknown [60] Primary Pulmonary DLBCL Data not available Data not available Data not available…”
Section: Extranodal Lymphomas Of Immune-privileged (Ip) Sitesmentioning
confidence: 86%
“…Further studies confirmed such remarkable site-specific occurrence of MYD88 mutation [55,56]. Gastrointestinal DLBCL <5% [60] 11% [40] Absent [40] Primary Bone DLBCL Absent [60] Absent [60] Absent [60] Thyroid gland DLBCL Absent [60] Absent [60] Absent [60] Head and Neck DLBCL Unknown [60] 3.17% (small sample size) [61] Unknown [60] Primary Pulmonary DLBCL Data not available Data not available Data not available…”
Section: Extranodal Lymphomas Of Immune-privileged (Ip) Sitesmentioning
confidence: 86%
“…Similarly, MAPK signaling inactivation contributes to a reduced the chance of COVID-19 [38,39]. Prior studies have suggested that elevated pro-inflammatory IL-17 is associated with elevated NOD-like receptor [40,41]. NOD-like receptor, one of the inflammatory components, can increase the expression of interleukin-1β [35].…”
Section: Results Of Molecular Dockingmentioning
confidence: 99%
“…In the study by Niu et al . [ 1 ] the MYD88 expressions in DLBCL were examined by performing immunohistochemical methods to evaluate MYD88 protein expression. Limited research has been performed by immunohistochemical method to detect expression of MYD88 protein.…”
Section: Discussionmentioning
confidence: 99%
“…The higher Bcl-2 expression was associated with positive MYD88 protein expression in the Niu et al . [ 1 ] study, which might show that Bcl-2 and MYD 88 expression impede apoptosis of tumour cells, encourage its proliferation, augmenting the other oncogenes’ role in lymphoma cells. The progress of lymphoma is accelerated by Bcl-2 protein, and it encourages lymphoma cell resistance to chemotherapy drugs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation